Determinants and Prediction of CO2 Emissions in Tunisia: LMDI Decomposition Approach of an Error Correction Model - Ben Hammamia, Amira; Dhakhlaoui, Ahlem (International Journal of Energy Economics and Policy, 2023)
In order to be able to meet the commitments with regard to its Nationally Determined Planned Contribution submitted to COP 21, Tunisia is committed to effectively reducing its CO2 emissions. Our study detects the main potential factors responsible for the increase in carbon dioxide emissions in Tunisia using the decomposition method (Logarithmic Mean Divisia Index: LMDI). Then, an analysis of the long-term relationship between CO2 emissions and these main factors is established through an error correction model. The forecast of this cointegration relationship by 2030 shows that Tunisia has significant potential for reducing CO2 emissions, especially through the phenomenon of reduction in energy intensity. However, political intervention beyond energy control is necessary in order to achieve Tunisia’s environmental objectives.